2021
DOI: 10.3390/ma14175090
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Influence of Hydraulic Additives on the Foaming Process and Stability of the Produced Geopolymer Foams

Abstract: The research described in this article was aimed at determining the influence of hydraulic additives on the foaming process and the stability of the produced geopolymer foams. These foams can be used as insulation materials to replace the currently commonly used insulations such as expanded polystyrene or polyurethane foams. Geopolymers have low thermal conductivity, excellent fire- and heat-resistant properties, and have fairly good mechanical properties. Research on foamed materials shows that they have the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…On the other hand, the GPC mix has the highest average density and thermal conductivity coefficient as well. This relationship has also been confirmed in a work [34].…”
Section: Calculated and Measured Porosity Characteristicssupporting
confidence: 70%
“…On the other hand, the GPC mix has the highest average density and thermal conductivity coefficient as well. This relationship has also been confirmed in a work [34].…”
Section: Calculated and Measured Porosity Characteristicssupporting
confidence: 70%
“…However, the decomposition of aluminum powder and silica fume generates hydrogen gas. The potential problems arise when the porous structure produced by foaming agents is stable only for a short time and then falls for a while (before the bonding process-geopolymerization) [17]. Moreover, the repeatability of the results obtained on an industrial scale is still regarded as a challenge of using geopolymer materials as insulators in buildings and other applications [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several researchers are done with the application of the same principle for determining the conductivity of geopolymeric concrete. For instance, Lach et al [70] have studied the thermal conductivity by varying the hydraulic additives; Kozub et al [71] have found that the addition of glass wool waste can reduce the thermal conductivity coefficient and the amount of 5% by weight of glass wool waste causes a reduction of −6.6% in relation to the reference sample.…”
Section: Thermal Testsmentioning
confidence: 99%